Effect of hydrostatic pressure and antimicrobials on survival of Listeria monocytogenes and enterohaemorrhagic Escherichia coli in beef. (December 2016) - Li, Hui; Gänzle, Michael
Abstract: The effects of marinades on Listeria monocytogenes and enterohaemorrhagic Escherichia coli were investigated in pressure treated beef steaks. Meat was treated with 600 MPa or 450 MPa. Marinades did not enhance pressure inactivation of E. coli in beef steaks and marinades prevented pressure-induced sublethal injury in L. monocytogenes . Membrane-active essential oils carvacrol and thymol, and thiol-reactive allyl-isothiocyanate (AITC) and cinnamaldehyde were selected to investigate potential synergistic activity of clean label antimicrobials with pressure . Carvacrol accelerated pressure inactivation of E. coli in beef steaks; however, carvacrol increased pressure resistance of E. coli in buffer, and had no effect on survival of E. coli in ground beef. Thymol had no effect in either buffer or meat. AITC and cinnamaldehyde exhibited synergistic activity with pressure on E. coli in buffer; however, cinnamaldehyde did not affect survival of E. coli after pressure treatment of meat. Synergistic inactivation of AITC with pressure was observed only at concentrations that are negatively affect meat quality. AITC and carvacrol may be practically applied for enhancing the bacterial inactivation and extending the shelf life of beef steaks. Highlights: Marinades did not enhance pressure inactivation of L. monocytogenes or E. coli . Membrane active and thiol reactive antimicrobials were investigated. Carvacrol accelerated the pressure inactivation of E. coli in beef steaks. AITC had strong synergism with pressure on E. coli in buffer and meat. CIN accelerated pressure inactivation of E. coli in buffer but not in meat.